LncRNA NEAT1 reversed the hindering effects of miR-495-3p/STAT3 axis and miR-211/PI3K/AKT axis on sepsis-relevant inflammation. (January 2020) - Xia, Demeng; Yao, Renqi; Zhou, Panyu; Wang, Chen; Xia, Yan; Xu, Shuogui
Highlights: High NEAT1 and low miR-495-3p/miR-211 expression were associated with TH + LPS. NEAT1, miR-495-3p and miR-211 modulate inflammatory cytokines after LPS-treated. NEAT1 could sponge miR-495-3p and miR-211 to play this pro-inflammatory role. Roles of NEAT1/miR-211 axis were partly mediated by PI3K/AKT signaling. Abstract: Objective: This investigation was intended to elucidate lncRNA-miRNA networks that could explain inflammation underlying sepsis progression. Methods: In the first place, four kinds of mice models were established, namely, SHAM group (n = 30), trauma (TH) group (n = 30), lipopolysaccharide (LPS) group (n = 30) and TH + LPS group (n = 30). Their lung, spleen and liver tissues were gathered for determination of TNF-α, IL-6, IL-10 and MCP-1 levels. Furthermore, mouse mononuclear macrophage leukemia cell line (RAW264.7) was stimulated by LPS to establish inflammation cell models. Then si-NEAT1s, pcDNA3.1-NEAT1, miR-495-3p mimic, miR-495-3p inhibitor, miR-NC, miR-211 mimic and miR-211 inhibitor were, respectively, transfected into the cells, so as to observe the impacts of NEAT1, miR-495-3p and miR-211 on cytokine levels released by the cells. Results: The survival condition of mice in the TH + LPS group was undesirable, in relative to mice in the LPS group and SHAM group (both P  < 0.05). High-level NEAT1 and low-level miR-495-3p/miR-211 were associated with poor survival of mice in the TH+LPS group ( P  < 0.05). Additionally, the correlation between NEAT1/miR-495-3p/miR-211 level and cytokine level was the strongest among TH+LPS-treated mice, in comparison to mice treated by TH or LPS. Furthermore, up-regulation of NEAT1 level and down-regulation of miR-495-3p/miR-211 level could aggravate inflammation in LPS-treated RAW264.7 cells. The miR-495-3p and miR-211 herein, were both subjected to sponging of NEAT1, possibly affected inflammation responses in RAW264.7 cells, respectively, through modulating STAT3 and PI3K/AKT signaling. Conclusion: LncRNA NEAT1 exhibited great potential sepsis diagnosis and treatment, considering its modifying miR-495-3p/STAT3 axis and miR-211/PI3K/AKT axis in inflammation cell models.